2010
DOI: 10.1162/jocn.2009.21229
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Neural Network Recruited by Expertise with Musical Notation

Abstract: Prior neuroimaging work on visual perceptual expertise has focused on changes in the visual system, ignoring possible effects of acquiring expert visual skills in nonvisual areas. We investigated expertise for reading musical notation, a skill likely to be associated with multimodal abilities. We compared brain activity in music-reading experts and novices during perception of musical notation, Roman letters, and mathematical symbols and found selectivity for musical notation for experts in a widespread multim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
113
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 80 publications
13
113
1
Order By: Relevance
“…In music reading, Wong & Gauthier (2010a) found stronger activation in musicians than in controls in the fusiform gyrus, slightly more mesial but only 2 mm off along the anteroposterior axis , as compared to the present results. These activations contrasting single notes versus letters and other symbols are described as posterior to letter-selective areas, but no coordinates are reported for the latter.…”
Section: Correlates Of Musical Expertisesupporting
confidence: 54%
See 3 more Smart Citations
“…In music reading, Wong & Gauthier (2010a) found stronger activation in musicians than in controls in the fusiform gyrus, slightly more mesial but only 2 mm off along the anteroposterior axis , as compared to the present results. These activations contrasting single notes versus letters and other symbols are described as posterior to letter-selective areas, but no coordinates are reported for the latter.…”
Section: Correlates Of Musical Expertisesupporting
confidence: 54%
“…This overall result is congruent with Muaykil et al (2015), who recently found left frontal and parietal activations in subjects with elementary musical competence, and with Stewart et al (2003), who found training effects of music reading in the left inferior parietal lobule. Wong & Gauthier (2010a), report bilateral activations in musical experts, and also mention left inferior parietal activations. The present study focusses on occipitotemporal processing, and it is out of our scope to speculate on the interpretation of whole-brain activations, beyond checking that our results fit with the literature.…”
Section: Correlates Of Musical Expertisementioning
confidence: 88%
See 2 more Smart Citations
“…neural selectivity | object recognition | individual differences | response reliability | ventral temporal cortex C ategory-selective responses in the visual system are found for several categories, including faces, limbs, scenes, words, letters, and even musical notation (1)(2)(3)(4)(5). However, a plausible argument can be made for a genetically determined brain system specialized for the representation of faces (6), which includes the fusiform face area (FFA).…”
mentioning
confidence: 99%